Analisis kepatuhan perawat pelaksana dalam penerapan dual identification patient - Nur Faiza Iswatiningtyas; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur; Suciati Suciati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Patient identification is one of the patient safety goals aimed at ensuring the accuracy of patient recognition before healthcare services are delivered. The implementation of dual patient identification is essential to prevent medication errors, incorrect procedures, and other medical incidents. However, nurses’ compliance with patient identification procedures remains a challenge in healthcare settings. Objective: To analyze nurses’ compliance in implementing dual patient identification. Methods: This study employed a descriptive observational case study design. Data were collected through questionnaires and direct observations conducted over three consecutive days using a patient identification checklist comprising nine indicators. Results: Questionnaire findings indicated that all nurses reported 100% compliance with all dual patient identification indicators. However, observational results demonstrated a decline in compliance over the three-day observation period, from 82.4% on the first day to 76.5% on the second day and 44.1% on the third day. Conclusion: Although nurses demonstrated good knowledge and understanding of dual patient identification, its implementation in daily practice was not yet optimal and was performed inconsistently.   Keywords: Dual Patient Identification; Hospital Safety; Nurse Compliance; Patient Identification; Patient Safety.